Phytochrome-mediated production of monoterpenes in thyme seedlings - Tanaka, S.; Yamaura, T.; Shigemoto, R.; Tabata, M.
Irradiation of either etiolated seedlings or detached cotyledons of thyme with red light strongly promoted the production of monoterpenes (thymol, ?-terpinene, p-cymene, and carvacrol). This photoresponse proved to be reversible by alternate irradiations with red and far-red light, suggesting for the first time the participation of phytochrome in the photoregulation of monoterpene production.
Keywords: THYMUS VULGARIS; LABIATAE; THYME; GLANDULAR TRICHOME; ESSENTIAL OIL; MONOTERPENE; THYMOL; BIOSYNTHESIS; LIGHT; PHYTOCHROME